Rain induced attenuation studies for 38 GHZ satellite link in tropical region - Khairayu Badron (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Satellite operations at 38 GHz in tropical and equatorial regions are constrained as a result of attenuation from rain. Measured statistics for 20 consecutive months of 38GHz terrestrial link signal attenuation measurements in Malaysia are presented in this thesis. In the absence of an actual satellite-Earth link, measured data acquired from a microwave link establishment should be able to provide some preliminary critical thoughts of the V-band link‟s characteristics. Such information is considered very pertinent for earth space communication link design and can be used for initial groundwork plan for the engineers as well as researchers. The measured attenuation statistics are then fittingly scaled up and compared with The ITU-R prediction models. Significant differences are evident between calculated attenuation with predicted values using the latest ITU-R models; which appear to underestimate the annual statistics. The statistics are then further explored to examine seasonal and diurnal variations. Characteristics of rain events such as fade duration, inter-fade interval and average duration are presented. It is essential to identify such characteristics for the design and implementation of future fade countermeasure techniques on satellite links. This thesis also reviews the current status of available propagation data and information relating to the design of satellite telecommunication systems in tropical regions. With broadcast application in mind, the seasonal and diurnal variability of rain attenuation was investigated in addition to the compilation of annual cumulative statistics. For instance, a satellite broadcast system may find greatest viewer demand during the late afternoon and evening hours, where in some climates highest rainfalls occur. Based on the rain attenuation and some scientific concerns on millimetre wave, a new model to predict rain attenuation in tropical region was developed. The model was configured taking consideration of the physical structure of the rain drops at 38 GHz frequency, type of precipitation and the scattering and absorption properties when attenuated by hydrometeors